Problems Encountered by Indonesian EFL Learners in Mastering Speaking Skills - Franscy Franscy; Ramli Ramli (Pioneer: Journal of Language and Literature, 2022)
The aims of this research are to analyze and find the linguistic and non-linguistic faced by Indonesian EFL learners in mastering speaking skill. This research uses a qualitative approach with descriptive analysis method. The researchers involved as observers and informants who directly engaged in this research. The research data were obtained by involving as the subjects of study. This research focuses on the problems experienced by students in mastering English speaking skill as the object of research. The data collection technique of this research was conducted by observation, interview, and documentation with main informants and additional informants. The researchers used the main data source from the informants’ interview to find out the problems faced by Indonesian EFL learners in mastering speaking skill. Result of the data indicated that Indonesian EFL learners experienced the problems both in linguistic and non-linguistic aspects. The linguistic aspects comprise of: (1) comprehension, (2) pronunciation, (3) vocabulary, (4) grammar and (5) fluency. Whereas the aspects of non-linguistic included; (1) nervous to speak, (2) no motivation, (3) afraid of making errors, and (4) low participation in class. The result of this research showed that the highest percentage that caused students' speaking mastery problems was the linguistic aspect, which reached 77% while the non-linguistic aspect only reached 23%.